The role of partnerships in regional and urban development at the turn of the century - Ronald W. McQuaid (European Regional Science Association (ERSA), 1998)
The term "partnership" is increasingly used in regionaldevelopmentalthough the practice of partnership in urban economic policy,if not theterminology, is common and has a long history. Currentlypartnershipsreceive widespread support from practitioners as they are seenas allowingeach partner to gain the benefits from co-operation, whilestill retainingtheir autonomy. However, the theoretical basis of these viewsis poorlydeveloped. This paper seeks to present an exploration of thetheoreticalbasis of regional and urban development partnerships and todraw resultinglessons for their improvement. From an analytical perspective,can beargued that in order to fully understand the behaviour andpolicies oforganisations involved in local economic development, it isnecessary toconsider their partnerships and the associated relationshipswith networksof other actors, including the flows of resources, power, andinformationwithin these networks.
Keywords: 330